Peran ASEAN Defence Minister Meeting Plus (ADMM PLUS) Sebagai Forum Diplomasi Pertahanan Di Kawasan Asia - Gilang P, M. Harviend (Jurnal Studi Diplomasi dan Keamanan, 2016)
The ADMM-Plus is a forum for ASEAN and its eight Dialogue Partners to strengthen security and defence cooperation for peace, stability, and development in the region. The initial ADMMPlus was convened in Ha Noi, Viet Nam, in 2010. The Defence Ministers then agreed on fve areas of practical cooperation to pursue under this new mechanism, namely maritime security, counter-terrorism, humanitarian assistance and disaster relief, peacekeeping operations and military medicine. To facilitate cooperation on these areas, Experts Working Groups (EWGs) are established. This paper aims to describe the role of ADMM Plus as an important platform for Asiaâs defence diplomacy. It argues that, like other ASEAN oï¬spring forums, the ADMM-Plus plays an important role in building confdence-building measures in the fve priority areas. It is, however, still unclear whether it could lead to next steps of defence cooperation.